Laura Ingalls Wilder's Juvenile Historical Fiction - Vtípilová, Aneta (Univerzita Pardubice, 2019)
This master thesis deals with the settlement of American West in the juveniles' historical fiction written by Laura Ingalls Wilder. Her novels from Little House series featuring the Ingalls family are the object of the literary analysis. Her works will be compared with the novel The Birchbark House by Louise Erdrich. The features of the life of pioneers on the American frontier are analysed on the works by Wilder. Wilder is compared to Erdrich for the completion of the view of the Native Americans. The goal of the thesis is to assess how Wilder depicted the settlement of American West.
Historické romány pro mládež Laury Ingalls Wilderové
Keywords: Americký západ; pohraničí; průkopníci; původní obyvatelé Ameriky; Malý dům; Wilderová, Laura Ingalls; American West; frontier; pioneers; Native Americans; Little House; Wilder, Laura Ingalls